(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The study included the collection of 200 urine samples from patients with urinary tract infection, and 130 isolates of Escherichia coli were diagnosed by relying on the principle of production to hemolysin enzyme. The isolates were collected from special laboratories in Baghdad, Iraq; the research isolate the bacteria that cause urinary tract infections and produce hemolysin. In addition, the research reaches urinary tract infections and reveal their molecular characteristics and pathogenic factors associated with pathogenicity, hemolysis, and resistance to antibiotic control factors.Urinary tract infections (UTIs) are widespread, an important cause of morbidity, and resistance to antibiotic therapy is increasing. Women disproportionately suffer a UTI: 50% of all women will have a UTI in their lifetime. Additionally, 20-40% of those women who have an initial UTI will experience a recurrence with some suffering recurring recurrences with a serious deterioration in quality-of-life pain and discomfort, disruption of daily activities, increased health care costs, and fewer treatment options other than long-term antibiotic prophylaxis.